Developing concept on sponge city arrangement for flood hazard mitigation: A case study of Wuhan, China - M.Y. Lin; S.L. Shen; W.C. Cheng (International Association of Lowland Technology, 2019)
As a frequently flooded city, Wuhan is one of the key cities that need to improve the abilities against flooding hazards. The recent rainstorms happened in Wuhan led to floods and threatened people’s lives as well as made huge economic losses so that it is urgent to develop an overall Sponge City System in Wuhan. This paper investigates the reasons that Wuhan frequently suffered from severe flooding hazards, including (1) flat topography, (2) heavy precipitation, (3) reduction of lake area, (4) decreased capacity of drainage system. By consideration of these conditions in Wuhan, specific methods based on Sponge City are recommended. According to overall consideration of waterlogging risk, flooding impacts and Sponge City effects, key regions that need to be given priority to develop Sponge City are proposed. Then, this paper proposes following Sponge City arrangement: (1) recovery of water ecosystem and water quality status in Wuhan is recommended. (2) Based on the existing gardens in urban area, adjustments of bio-retention or rain gardens including increasing the proportion of rain gardens in residential regions and along lakes are proposed. (3) GIS is used to analyze the topography, build rain flood model based on DEM and monitor the waterlogging in order to reduce flooding hazards and improve the ecological environment in Wuhan. By analysis and constructions of Sponge City in Wuhan, the harmful effects of flooding will be reduced and the ecological environment will be improved.